ANALISIS PELAKSANA TUGAS PEJABAT SEMENTARA (PJS) KEPALA DESA DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI TAHUN 2014 - Firnanda, Restu; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Practice Designation of Acting (PJS) in an environment of village government still maintained until now. In Kuantan Singingi even contain it in legal products, namely Singingi Kuantan District Regulation No. 4 of 2009. In Article 46 paragraph (7) states that "after the dismissal of the chief, the Regent raised Acting Head of the village with the principal task of holding Elections Village head most 6 (six) months after delivery of the Decree as Acting Chief. The research problems are how the duties and authority of Acting (PJS) Head of the village in the district of Pangean Regency Kuantan Singingi governance and how the village after the stipulation of Acting (PJS) Head of the village in the district of Pangean Regency Kuantan Singingi.The research location is in the district of Pangean Regency Kuantan Singingi. The method used is qualitative research, data collection techniques are interviews, observation and documentation.Based on the survey results revealed that during the leadership of Acting (PJS) Village Head in the village of Pasar Baru, Pulau Kumpai and the village of Padang Kunik not carrying out the duties and authority as it should be, so that the condition of the village is not working properly in accordance with the purpose of government and rural communities in particular, and the resulting adverse impact such instability village conditions. Village government organization after the establishment of Acting (PJS) Head of the village in the district of Pangean Regency Kuantan Singingi impact in the fields of administration, regulatory areas of the village, and the village chief Decision Division.Keywords : village government, Duties Acting (PJS)